Signal processing using optics - Bradley (Oxford University Press, 1998)
Signal Processing Using Optics covers the fundamental aspects of optical signal processing at an introductory level and also discusses more applied topics, helping students and professionals bridge the gap to the current technical literature. Although readers are expected to have previous knowledge of one-dimensional signals and systems and optics beyond general physics, this self-contained text reviews the essentials of signal processing, optics, and imaging to make necessary background information readily available